Efeito da carga elástica nas estratégias cinemática e eletromiográfica dos movimentos de flexão-extensão dos ombros realizados no aparelho Reformer segundo o método pilates - Costa, Lívia Alice Ramalho (2010)
The Pilates exercises can be performed in soil and equipment. The equipment, they are executed against the resistance of springs (elastic load), which require an additional complexity to the implementation and control of movements. Despite the scope of the method employed in rehabilitation, there are few scientific studies that prove its effectiveness. This range demonstrates the use of the method, by itself, the need for a description of motor control and biomechanics of the exercises, allowing an understanding of kinesiology same. Objectives: Identify and describe strategies for modulation of kinematic and EMG activity of major muscles during performance of shoulder movement with reversal performed upon the demand of different elastic loads on the Reformer equipment by individuals not practicing Pilates. Methods: Eight female volunteers participated in this study. Were instructed to perform a task of extension and flexion in the Reformer apparatus according to Pilates, resistance against the three magnitudes of tensile load (spring). The kinematics of the shoulder angle and linear kinematics of the equipment were reconstructed using an optical three-dimensional motion analysis (OPTOTRAK 3020) and EMG activity of major muscles were collected using surface electrodes (Deslys). The results showed that subjects spent more time decelerating phase of the IDA for the three charges. In general, we found that with increasing tensile load the less time that the subject takes to perform the task. The EMG activity of muscles, anterior deltoid, posterior deltoid and rectus abdominis increased with increasing tensile load.